2023
DOI: 10.2478/abm-2023-0051
|View full text |Cite
|
Sign up to set email alerts
|

Infection rate among close contacts of patients with coronavirus disease in Japan: a descriptive study and literature review

Osamu Yamamura,
Hidenori Onishi,
Ippei Sakamaki
et al.

Abstract: Background In Japan, on April 20, 2020, the definition of a close contact regarding coronavirus disease (COVID-19) was changed from a long-term contact time to a specified contact time of 15 min and from a contact distance of 2 m to 1 m. Objectives We aimed to determine the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection rate among close contacts of patients with COVID-19 and determine the impact of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…Yamamura et al [6] in this issue investigate the infection rate among close contacts of patients with coronavirus disease in Japan. They found that the infection rate showed a rising trend from 11.1% in period 1 to 19.2% and 20.0% in periods 2 and 3, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamura et al [6] in this issue investigate the infection rate among close contacts of patients with coronavirus disease in Japan. They found that the infection rate showed a rising trend from 11.1% in period 1 to 19.2% and 20.0% in periods 2 and 3, respectively.…”
mentioning
confidence: 99%
“…They found that the infection rate showed a rising trend from 11.1% in period 1 to 19.2% and 20.0% in periods 2 and 3, respectively. The authors speculated that one important factor of the rising trend in infection rate was the change in definition used for close contacts in Japan [6]. In addition, the variants differed between the periods [7] and some variants, such as the Omicron, have been shown to have strong immune escape [8].…”
mentioning
confidence: 99%